Cervicomedullary Junction Ependymoma Associated with Neurofibromatosis Type II: Case Report and Literature Review - Silva, Otavio Turolo da; Miranda, Carlos Eduardo Vasconcelos; Joaquim, Andrei Fernandes; Queiroz, Luciano de Souza; Ghizoni, Enrico; Tedeschi, Helder (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Neurofibromatosis type II (NF2) is a rare autosomal dominant inherited disease caused by a mutation in chromosome 22q12 and associated with multiple central nervous system tumors. In this paper, we describe a rare case of cervicomedullary junction ependymoma associated with NF2 in a 25-year-old man who underwent surgical treatment with total resection and had a good clinical outcome. We discussed the nuances of the surgical resection and the literature concerning this rare form of presentation of NF2.
Keywords: neurofibromatosis type II; ependymoma; surgery